An in vitro strategy using multiple human induced pluripotent stem cell-derived models to assess the toxicity of chemicals: A case study on paraquat. (June 2022) - Nunes, Carolina; Singh, Pranika; Mazidi, Zahra; Murphy, Cormac; Bourguignon, Aurore; Wellens, Sara; Chandrasekaran, Vidya; Ghosh, Sreya; Zana, Melinda; Pamies, David; Thomas, Aurélien; Verfaillie, Catherine; et al.
Abstract: Most OECD guidelines for chemical risk assessment include tests performed on animals, raising financial, ethical and scientific concerns. Thus, the development of human-based models for toxicity testing is highly encouraged. Here, we propose an in vitro multi-organ strategy to assess the toxicity of chemicals. Human induced pluripotent stem cells (hiPSCs)-derived models of the brain, blood-brain barrier, kidney, liver and vasculature were generated and exposed to paraquat (PQ), a widely employed herbicide with known toxic effects in kidneys and brain. The models showed differential cytotoxic sensitivity to PQ after acute exposure. TempO-Seq analysis with a set of 3565 probes revealed the deregulation of oxidative stress, unfolded protein response and estrogen receptor-mediated signaling pathways, in line with the existing knowledge on PQ mechanisms of action. The main advantages of this strategy are to assess chemical toxicity on multiple tissues/organs in parallel, exclusively in human cells, eliminating the interspecies bias, allowing a better evaluation of the differential sensitivity of the models representing the diverse organs, and increasing the chance to identify toxic compounds. Furthermore, although we focused on the mechanisms of action of PQ shared by the different models, this strategy would also allow for organ-specific toxicity testing, by including more cell type-specific probes for TempO-Seq analyses. In conclusion, we believe this strategy will participate in the further improvement of chemical risk assessment for human health. Graphical abstract: Unlabelled Image Highlights: A human iPSC-derived organ/tissue-specific model strategy for toxicity testing is proposed. Human iPSC-derived organ/tissue-specific models showed different sensitivity to paraquat. Oxidative stress, unfolded protein response and estrogen-mediated signaling pathways were deregulated.